Teaching Factory Management in the Industrial Era 4.0 in Indonesia - Agus Alamsyah Perwiranegara (International Journal of Science and Society, 2022)
The emergence of the industrial era 4.0 led to the need for changes in the world of education to compensate for the increase in this industry. Teaching factory learning itself has a function to be able to prepare graduates who the industry can immediately absorb. To see the success of the teaching factory, a comprehensive evaluation is needed so that the strengths and weaknesses of the teaching factory can be known. This study uses a descriptive approach based on a literature review. The research data were obtained from various research results and previous studies still relevant to this research. From the results of this study, it was concluded that the implementation of the teaching factory was still not running correctly because there was no common understanding regarding the teaching factory learning pattern among the parties concerned. In addition, there are limitations in resources, so as a result, schools have difficulties implementing optimal teaching factories.